Self regulation of single mother having child with autism in Banda Aceh - Sitti Wahyuni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Self-regulation is needed in every individual, especially the single mothers who have child with autism. Good self-regulation of the single mother who have child with autism will have an important impact in helping children with autism to growing well. The research objective is obtaining the dynamics of selfregulationin the single mothers who have child with autism in Banda Aceh, by used qualitative research methods to the two respondents of research. Collect data by interviewing the respondents for ± 1.5 months. Analyze the data using the analysis case of per-respondent in narrative description. The research showed each respondent had different self-regulation, it is caused by differences in the chronology of case that has happened, differences in feelings of each respondent to accept this case, and differences in interpretation by each respondent in this case.